Password to Larkspur Lane - Keene, Carolyn (New York : Grosset & Dunlap, 1966)
A puzzling message attached to the leg of a wounded homing pigeon involves Nancy in a dangerous mission.
5-8
660L
6.4
Keywords: Mystery and detective stories; Swindlers and swindling -- Fiction; Drew, Nancy (Fictional character) -- Fiction